The new etiology and surgical therapy of stress urinary incontinence in women. (February 2020) - Ostrzenski, Adam
Abstract: Objectives: To determine the subjective and objective cure rate of a urethral stabilization procedure (USP) for stress urinary incontinence (SUI) in women; to describe this new surgical intervention; to record its potential complications; to establish the SUI etiology. Study Design: The author conducted a prospective case series study in ambulatory settings and under local anesthesia. Thirty-four consecutive women with uncomplicated SUI subjected to USP, which was performed by reconstructing site-specific defects within the urethral stabilizing mechanism (USM) and using no surgical slings, meshes or absorbable sutures. The paravaginal defect(s) was repaired by transvaginal approach. The endopelvic fascia was sharply separated from the ventral perineal membrane (VPM) just above the anterior urethral meatus. The vestibular bulbs sharply dissected from VPM and advance upwards. The VPM defect(s) reconstructed and vestibular bulbs placed back to the original location. The access to the peri- and the para-urethral region was created by making a lateral vertical incision, aside from the lateral urethral meatus and defects were repaired. The suburethral transverse incision was made beneath the urethral meatus and the stratum-by-stratum surgical dissection conducted until the lateral vaginourethral ligament is visualized bilaterally. The defect(s) within the vaginourethral ligaments was surgically reconstructed, and the vaginal wall repaired. The primary outcome measured subjective and objective cure rates, and the secondary outcome measured the occurrence of potential complications. The five-year postoperative follow-up was conducted. Results: Two out of thirty-four patients dropped-out from the study. The USP performed without difficulties, and no severe complication observed. One-subject developed superficial wound separation (3.1 %) and one-subject (3.1 %) developed urinary urge incontinence at the 5-postoperative-year. At 60-month follow-up subjective and objective cure rates were a 92 % and an 88 % respectively. Conclusions: The urethral stabilization procedure yields a high degree of subjective and objective cure rates without severe complications and is a well-tolerated operation by women. The urethral stabilization procedure is a simple, easy to implement, and reproducible method for uncomplicated stress urinary incontinence in women. Site-specific defects within the urethral stabilizing mechanism constitute the etiology of the stress urinary incontinence in women.